PENGEMBANGAN JURNAL PERAWATAN HARIAN DAN PERBAIKAN POMPA WALRUS TPH 2T 3K PADA MESIN CNC SMK STMI BANDA ACEH BERDASARKAN STANDAR KOMPETENSI NASIONAL - ferri festika; Budi Perdana Putra; Afdhalul Rajai; Misswar Abd (Prodi Teknik Mesin Fakultas Teknik Universitas Iskandar Muda, 2025)
The Krisbow VDL-1000 CNC machine at SMK STMI Banda Aceh experienced a cooling system failure due to coolant leakage from the Walrus TPH 2T 3K multistage centrifugal pump. The leakage occurred at the flange connection between the motor and pump body, causing pressure drop and coolant flow stoppage. This study aims to document the repair procedure and develop a daily maintenance log template based on SKKNI, specifically units IMG.PM02.008.01 (Performing Machine Repair) and IMG.PM02.007.01 (Planning Machine Maintenance). The methodology includes field observation, technical manual analysis of Walrus pumps, and implementation of repair procedures using non-asbestos gasket replacement. Results show that adding a 1.5 mm non-asbestos gasket completely stopped the leakage. The developed journal template includes daily checklist, repair actions, result verification, and K3LL documentation, making it suitable for operational guidance in vocational schools and industry, as well as evidence of student and teacher competency.